2021
DOI: 10.1007/s12035-021-02620-6
|View full text |Cite
|
Sign up to set email alerts
|

Adult Neural Stem Cell Migration Is Impaired in a Mouse Model of Alzheimer’s Disease

Abstract: Neurogenesis in the adult brain takes place in two neurogenic niches: the ventricular-subventricular zone (V-SVZ) and the subgranular zone. After differentiation, neural precursor cells (neuroblasts) have to move to an adequate position, a process known as neuronal migration. Some studies show that in Alzheimer’s disease, the adult neurogenesis is impaired. Our main aim was to investigate some proteins involved both in the physiopathology of Alzheimer’s disease and in the neuronal migration process using the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…This research group found an increase in Cdh1 levels and a decrease in Cdk5/p35 and cyclin B1, which is evidence that these cells exhibit an alteration of the cell cycle. Furthermore, they found fewer cells in the RMS and fewer OB neurons, according to the deficit in cell migration and the decrease in odor discrimination ( Figure 1 A) [ 108 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…This research group found an increase in Cdh1 levels and a decrease in Cdk5/p35 and cyclin B1, which is evidence that these cells exhibit an alteration of the cell cycle. Furthermore, they found fewer cells in the RMS and fewer OB neurons, according to the deficit in cell migration and the decrease in odor discrimination ( Figure 1 A) [ 108 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…In particular, decreased proliferation of adult NSCs is induced by intracellular Aβ oligomers ( Scopa et al, 2020 ). Investigation of adult SVZ neurogenesis in APP/PS1 mice, which are known to exhibit Aβ deposition from 6 weeks of age and cognitive impairment at 7 months of age, showed that the proliferation and migration of NPCs decreased in the SVZ when the mice were 3 and 6 months old ( Esteve et al, 2022 ). Studies using 2-month-old APPswe/PS1ΔE9 mice demonstrated that proliferation of NPCs and migration of neuroblasts significantly decreased in the SVZ ( Demars et al, 2010 ).…”
Section: Subventricular Zone Neurogenesis In Alzheimer’s Diseasementioning
confidence: 99%
“…In addition, the proliferation of adult NSCs was dramatically reduced in the Aβ-injected cortex compared with the contralateral cortex in Aβ-injected mice ( Haughey et al, 2002 ). Specifically, Aβ inhibits the proliferation of adult NSCs originating from the SVZ by downregulating the expression of positive cell cycle modulators, including CDK5/p35 and cyclin B1, and upregulating the expression of the negative modulator Cdh1 ( Esteve et al, 2022 ). Accumulated findings in an AD mouse model indicate that Aβ is a powerful factor that reduces adult SVZ neurogenesis by inhibiting the cell cycle, thereby inhibiting cell proliferation.…”
Section: Subventricular Zone Neurogenesis In Alzheimer’s Diseasementioning
confidence: 99%
“…Cdh1 loss shortens G1 phase and enhances S phase, leading to replicative stress and p53-mediated apoptosis of neural progenitor cells ( Delgado-Esteban et al, 2013 ). Recently, Esteve et al (2022) found increased Cdh1 levels, decreased cyclin B1 levels, and reduced proliferation of neuronal progenitors in the ventricular-subventricular zone of AD mice, which triggers senescence. Adult neurogenesis stimulation by the regulation of Cdh1 and/or cyclin B1 levels might be important to modify AD progression.…”
Section: Apc/c-cdh1 Targets In Alzheimer’s Disease Pathologymentioning
confidence: 99%